METHODS TO FIND COORDINATES OF OIL WELLS – CONTAMINATORS OF THE ENVIRONMENT - Semchuk, Ya. M.; Lialiuk-Viter, H. D.; Kryvenko, G. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We have analyzed methods that are used to locate oil wells which pollute subsurface water. The main method to find coordinates is to run indicators in a well. It has been found out that a substance which would be absent in natural water should be selected among the range of chemical indicators. The selection of certain dyes is determined by physical and chemical properties of aquifers in order to eliminate sorption and dispersion processes. Two types of field research are recommended. The first scheme involves putting of the indicator into the well under conditions of natural flow, and the second scheme is the injection of substance into the well. The article points out the drawbacks of this method. It has also examined hydro chemical method to determine the coordinates which is based on the chemical analysis of samples taken from wells. We have also analyzed the method which uses hydrodynamic research to determine sources of contamination of aquifers. That is to disturb static equilibrium in the aquifer by intensive sample taking from the well which is the contamination source.